Pulmonary infarct as a initial presentation of acute myeloid leukemia: a diagnostic difficulty - Anandan, Jeevanandham; Upadhya, Pratap; Vemuri Mahesh Babu; Basu, Debdatta; Vidhyalakshmi Rangarajan (International Journal of Research in Medical Sciences, 2023)
The incidence of acute myeloid leukemia (AML) is age dependent and increasing among the patient groups aged above 60 years. The overall presentations in a case of AML is due to marrow infiltration of leukemic cells which results in fever and chills due to neutropenia, bleeding due to thrombocytopenia, fatigue and weakness due to anemia. Incidence of venous thromboembolism is very rare in hematological malignancies. We describe a case of adolescent male presented with features of lung consolidation later found to be a pulmonary infarct and finally diagnosed to have acute leukemia (AL).